WET DUST CLEANER RESEARCH OF HYDRODYNAMIC REGIME - O‘lmasov Farrux Yorqinjon o‘g‘li; Xonazarov Ro‘zmuxammad Dilshodjon o‘g‘li (American Journals Publishing, 2025)
The article describes a device that generates a contact element current that purifies dusty gas in a wet manner. Theoretical research work on determining the total hydraulic resistance is presented. A calculation scheme of the device for theoretical calculation work is developed. The equations of hydraulic resistance affecting the fluid flow according to the nozzle hole and diameter of the calculation scheme are presented.
Keywords: Wet method, spark flow, spark generator, contact element, dusty gas, toxic gas, air flow, gas flow, gas velocity, cyclone, dusty air, fan, cone mesh, disperser, biological microscope